Early versus late decompressive craniectomy in large middle cerebral arterial infarct- A stitch in time saves nine - Degaonkar, Amol Vijay; Gupta, Vijay Kumar; Carvalho, Ajay Sebastian; Sareen, Rateesh (Nepal Journal of Neuroscience, 2023)
Introduction: The etiology of malignant MCA infarctions is mostly due to thrombosis or embolic occlusion of either the internal carotid artery or the proximal MCA. The cornerstone of ischemic stroke diagnosis remains the history and neurological examination. A prospective study to compare outcome of early verses late decompression craniotomy was done at a tertiary care hospital in India.Materials and methods: A prospective observational study in the neurosurgical department of a tertiary care hospital of India, for a period of 3 years from 2018-2021. A total of 30 patients (15 each for early and late decompressive craniectomy respectively) were included in study after fulfilling inclusion criteria. The patients were followed up for next 6 months with  neuro examination and score making  done after every 1 month, 3 months and 6 months of-decompressive craniotomy. To find the significance between early and late group of patients we have used 2 independent sample t-test for age. For MRS and Barthal index at 1st month, 3rd month and 6th month, Hospital stay we have used Mann-Whitney U test (Non-parametric test) because the data type is ordinal or not following normal  Distribution/ skewed. All statistical test performed at 5% level of significance so the p-value < 0.05 considered as significant.Results: The majority of patients were male in both the groups – early group 9 (60%) and late group 12 (80%). The mean age group for early and late groups was 44.07 and 42.87 years respectively. The comparison of MRS score in early and late group was not statistically significant at 1st month of follow up, however it showed significant difference at 2nd and 6th month respectively. MRS score with respect to affected side, in both the early and late group showed statistically significant difference at 6 months of follow up respectively. The Barthel index with respect to affected side showed significant difference in early group whereas in the late group significant difference was seen at 6th month of follow up only. The outcome of patients was not affected by side of involvement in both groups early as well as late. The mean hospital stay in early group was 14.8 days in comparison to late group where it was 42.47 days.Conclusion: The results of the present study indicate that early surgical intervention for decompression craniectomy in cases of MCA infarct have better outcome than late intervention with shorter hospital stay better functional outcome at discharge and 6 months post discharge.